2022
DOI: 10.1089/cyber.2021.0148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Nomophobia and an Analysis of Its Contributing Factors in the Undergraduate Students of Pakistan

Abstract: BACKGROUND: Nomophobia (no-mobile-phone phobia) is a relatively new term that describes the growing fear and anxiety associated with being without a mobile phone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…A high proportion of participants had Moderate and Severe levels of nomophobia (47.1% and 44.1% respectively) (Table 3). This finding was in line with a study conducted in Pakistan by Farooq et al, 2022 who reported that (48.57 %) of their studied group had Moderate, and (40.88 %) had Severe NMP. However, the detected prevalence was lesser than those reported in other studies done by Kubrusly et al (2021) in Brazil and Kumar et al (2021) in India (64.5% and 74.8% respectively) who had Moderate nomophobia.…”
Section: Discussionsupporting
confidence: 92%
“…A high proportion of participants had Moderate and Severe levels of nomophobia (47.1% and 44.1% respectively) (Table 3). This finding was in line with a study conducted in Pakistan by Farooq et al, 2022 who reported that (48.57 %) of their studied group had Moderate, and (40.88 %) had Severe NMP. However, the detected prevalence was lesser than those reported in other studies done by Kubrusly et al (2021) in Brazil and Kumar et al (2021) in India (64.5% and 74.8% respectively) who had Moderate nomophobia.…”
Section: Discussionsupporting
confidence: 92%
“…In the United Kingdom (UK), the UK post office reported that around 53% of the population suffer from anxiety and fear when disconnected from their smartphone [13]. Similarly, other studies reported a high prevalence rate of nomophobia among students and health care professionals [14][15][16]. However, data on the prevalence and factors associated with Nomophobia in the middle east among the general population are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of deaf and hard-of-hearing (DHH) children in Saudi Arabia discovered that nomophobia was more common in female DHH youth than in males [20]. Similarly, in a study of undergraduate students in Pakistan, women reported greater levels of nomophobia compared to men [21].…”
Section: Discussionmentioning
confidence: 99%